Near‐3‐MeV protons from target‐normal‐sheath‐acceleration femtosecond laser irradiating advanced targets. Issue 7 (4th February 2019) - Torrisi, L.; Cutroneo, M.; Rosinski, M.; Badziak, J.; Parys, P.; Wołowski, J.; Zaraś‐Szydłowska, A.; Torrisi, A.
Abstract : Advanced targets based on graphene oxide and gold thin film were irradiated at high laser intensity (10 18 –10 19 W/cm 2 ) with 50‐fs laser pulses and high contrast (10 8 ) to investigate ion acceleration in the target‐normal‐sheath‐acceleration regime. Time‐of‐flight technique was employed with SiC semiconductor detectors and ion collectors in order to measure the ion kinetic energy and to control the properties of the generated plasma. It was found that, at the optimized laser focus position with respect to the target, maximum proton acceleration up to about 3 MeV energy and low angular divergence could be generated. The high proton energy is explained as due to the high electrical and thermal conductivity of the reduced graphene oxide structure. Dependence of the maximum proton energy on the target focal position and thickness is presented and discussed. Abstract :